Reabsorción de nitrógeno y fósforo foliar en árboles de bosques montanos en los Andes centrales de Colombia - Miguel Vera; Jaime Cavelier; Johanna Santamaría (Revista de Biología Tropical, 1999)
Se determinaron las concentraciones y los porcentajes de reabsorción de nitrógeno y fósforo foliar en cinco especies de árboles de un bosque montano bajo (BMB) a 1850 m.s.n.m. y en cinco de un bosque montano alto (BMA) a 2800 m.s.n.m en la Cordillera Central colombiana, asi como la disponibilidad de nitrógeno y fósforo del suelo. Los porcentajes de reabsorción de N y P no fueron significativamente diferentes entre las especies de estos dos bosques. A pesar de esto, se observó que la reabsorción de P foliar tendió a ser mayor en las especies del BMB donde la concentración de P en el suelo fue significativamente más baja (3.2 ppm vs. 9.0 ppm). Cuando la reabsorción de P foliar se expresó como función de la concentración en hojas maduras en 12 tipos de bosques montanos tropicales, se encontró una correlación negativa y estadísticamente significativa. Estos resultados sugieren que los porcentajes de reabsorción de P foliar en bosques montanos estarían controlados parcialmente por la disponibilidad del elemento. Mature leaves and litterfall were collected between November 1992 and February 1993 from one to three individuals of five canopy tree species of a lower montane rain forest (LMRF) at 1850 m. and five canopy tree species of an upper montane rain forest (UMRF) at 2800 m. in the Central Andes of Colombia, to determine the concentrations and percentage retranslocation of nitrogen and phosphorus. The availability of these two nutrients was measured in the soils, by means of extracts of NH3-NH4, NO2-NO3 and PO4, and incubations of surface soil samples (0-10 cm) to measure the rates of nitrogen mineralization and nitrification. In the species of the LMRF the average concentration of N in mature leaves (1.19 % dry weight) and litterfall (0.87 %) was significantly higher than in mature leaves (0.90 %) and litterfall (0.59 %) of the tree species of the UMRF. Percentage retranslocation of N and P were not significantly different between the species of these two forests. In spite of this, P retranslocation tended to be higher in the species of the LMRF where the available P in the soil was significantly lower (3.2 ppm vs. 9.0 ppm). A negative and statistically significant correlation was found between the percentage retranslocation of P and the concentration of this element in mature leaves of 12 different tropical montane forests. These results suggest that percentage retranslocation of foliar P in montane forests, could be partially controlled by the availability of this element. There were no statistically significant correlations between percentage retranslocation of N and P and specific leaf area for the ten tree species of this study. The lack of correlation may be the result of a small sample size and should be explored with a higher number of species.